Mitigation of Student Deviant Behaviour through Al-Ghazali’s Perspective Spiritual Values in the Disruptive Era - Bali, Muhammad Mushfi El Iq; Ruzifah, Devi (Jurnal Pendidikan Progresif, 2021)
Mitigation of Student Deviant Behavior through Al-Ghazali’s Perspective Spiritual Values in the Disruptive Era. Objectives: This study aims to provide an idea of the importance of internalizing spiritual values as a remedy for students’ deviant behaviour in a disruptive era. Methods: The method used in this research is library research. Sources of data used are libraries or documentaries in the form of books, scientific journals, translated books, and the internet. Findings: The results showed that the internalization of spiritual values from the perspective of Al-Ghazali in overcoming deviant behaviour of students in the disruptive era can be done by four methods including: Uswatun Hasanah (absence), Ta’wid (habituation), Mau’idzah (advice), Qishshah (story), by measuring the values of Aqidah, Syari’at and Morals. Conclusion: in internalizing spiritual values, cooperation between parents, teachers and the environment is needed to support and guide students towards a better direction for the realization of civilizes and disruptive human being.Keywords: spiritual values, deviant behaviour, disruptive era DOI: http://dx.doi.org/10.23960/jpp.v11.i1.202106